Highly Stretchable Micro/Nano Wrinkle Structures for Infrared Stealth Application - Jia Wang (Nanoscale Research Letters, 2018)
Abstract We demonstrate a novel infrared stealth structure consisting of SiO2/TiO2 film, which was manufactured as the highly stretchable triangular wrinkle structures. The triangular wrinkle structures have firstly been transferred to the flexible substrate from the surface of Si-substrate, which was manufactured by the MEMS technology. Then, the infrared reflective film have been manufactured to be the triangular wrinkle structures by depositing the materials (noble metal (Ag or Au) or multilayer oxide (SiO2/TiO2)) on the surface of flexible substrate. Due to the lower reflection effect of curved surface, the infrared reflectivity of these structures has been tuned down to 5%. And, compared to the flat surface, the reflection-to-diffuse ratios improved approximately one order of magnitude. These structures can adapt to the environment by changing the reflectivity of triangular wrinkle structures under stretching. Finally, an Au-modified infrared stealth structure has been fabricated as the array structures, which disappeared and then display by stretching the triangular wrinkle structures at room temperature. It features high reflection-to-diffuse ratios, stable repeatability, low-cost, and easy to manufacture. It may open opportunities for infrared camouflage for military security and surveillance field application.